URBAN SOCIETY IN POETRY “TELEPON GENGGAM” BY JOKO PINURBO (MASYARAKAT URBAN DALAM PUISI “TELEPON GENGGAM” KARYA JOKO PINURBO) - Maulina, Intan; Saragih, Mery Chris Isabella; Hutapea, Bilferi (Jurnal Gramatika, 2019)
This study discusses the reflection of life and urban society has a very close relationship; moreovermodern literature very often discusses the behavior of urban society in poetry. There are 30 poemswritten in Joko Pinurbo's book, and there are some of them which show how the urban communityrelates to their environment. The purpose of this study is to describe social portraits of urbancommunities in poetry and their relation to the realities that exist in society, as well as technologicaladvancements and lifestyle. This study uses descriptive methods to describe the state of the objectunder study by describing the things that are the center of attention and support the object of theresearch. The results of this study found 10 poems from 30 poetry titles in the Joko Pinurbo bookthat showed how the lives of people in urban society, their habits and how they relate to thecommunity in their environment. Jokpin's narratives bring the reader aware of how far urbansociety is with their environment. The results of this study can be used as a reference for the generalpublic.